2022
DOI: 10.1039/d1tc05632h
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature dielectric polymer composite films of all-organic PVDF/ABS with excellent energy storage performance and stability

Abstract: High-temperature dielectric for capacitive energy storage are highly desirable in modern electronic systems. However, the energy storage capability of most emerging polymers decreases quickly at heightened temperature. Here, linear Poly(acrylonitrile...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The results demonstrated that the organic fillers exhibited better compatibility with PVDF than the inorganic fillers and further helped to suppress the breakdown damage at the interface. Wen et al 28 introduced poly(acrylonitrile butadiene styrene) (ABS) into PVDF. The composites possessed excellent energy storage (U d maintained 11.42 J cm À3 at 100 1C) due to the intermolecular interaction between ABS and PVDF (CRNÁ Á ÁC-H) and the introduction of deeps traps.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that the organic fillers exhibited better compatibility with PVDF than the inorganic fillers and further helped to suppress the breakdown damage at the interface. Wen et al 28 introduced poly(acrylonitrile butadiene styrene) (ABS) into PVDF. The composites possessed excellent energy storage (U d maintained 11.42 J cm À3 at 100 1C) due to the intermolecular interaction between ABS and PVDF (CRNÁ Á ÁC-H) and the introduction of deeps traps.…”
Section: Introductionmentioning
confidence: 99%
“…Figure a,b illustrates the comparison of this paper with data from other literature. By comparing with other literature, it is easy to find that the PVDF/MG composite prepared in this paper has a significant improvement in discharge energy density and maintains a high charge/discharge efficiency under a high electric field. This work uses a PMMA-like linear MG copolymer to enhance the energy storage performance of PVDF.…”
Section: Resultsmentioning
confidence: 99%
“…They also present large-scale processability and controllable quality due to the preferable miscibility of two polymers. [170] All-organic multilayered polymer dielectrics Adv. Funct.…”
Section: All Organic Multilayered Polymer Dielectricsmentioning
confidence: 99%